Unjuk Kerja Resapan Air Hujan - Barid, Burhan; Nugroho, Prasetyo Adi; Huda, Asri Lutfi (Semesta Teknika, 2012)
Nowadays, the environmental problems that often occur are flood in wet season and drought in dry season. This happens because the rainwater runoff cannot seep into the ground well and the ground water level is decreased.Â  Excessive surface runoff can be reduced by a simple water infiltration wells on the land. To determine the efficiency of absorption well, a model was created using infiltration rainfall simulator unit to create the condition of heavy rain. This study aims to analyze the relationship between times and several parameters: soil moisture, the changes in the groundwater table, the runoff time, the volume of rainfall infiltration, and to determine the reliability of models with changes in water table. The study was conducted using the infiltration model unit which was made of steel plate with a size of 170x170x200 cm3. This model is divided into three spaces. The first space, which its size is 150x150x200 cm3, has two tests. The first one is labeled as A test and filled with medium silt with the elevation of -150 cm. The B test is filled with medium clay with the elevation of -125 cm. The second space, with the dimension of 170x20x200 cm3, is used to control the ground water level. The third space is used for measuring absorption capability and has dimension of 30x30x100 cm3. This model has nine holes on each side for measuring soil moisture and the 12th hole underneath is used for measuring changes in ground water level. After the artificial rain descended for 120 minutes, soil moisture and ground water level changes measured in every 10 minutes.